1973
DOI: 10.2527/jas1973.37118x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Purebreds and Two-Breed Crosses in Swine: Feedlot Performance and Carcass Merit

Abstract: Summary FEEDLOT performance of 941 barrows and gilts and carcass traits of 190 barrows of purebreds and crossbreds of the Duroc, Hampshire and Yorkshire breeds were evaluated for differences between purebreds and reciprocal crosses and for heterosis. Purebred and crossbred litters were farrowed contemporaneously at the Ft. Reno Experiment Station in the 1971 spring and fall farrowing seasons.Rather distinct differences between the pure breeds were evident for most traits. In general, Durocs gained weight more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 9 publications
3
14
0
Order By: Relevance
“…The gilts were randomly selected from litters produced in Phase I of the project. Information concerning the foundation herds and the production and subsequent performance of the purebred and two-breed cross gilts used in this study has previously been reported (Johnson et at, 1973;Johnson and Omtvedt, 1973b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gilts were randomly selected from litters produced in Phase I of the project. Information concerning the foundation herds and the production and subsequent performance of the purebred and two-breed cross gilts used in this study has previously been reported (Johnson et at, 1973;Johnson and Omtvedt, 1973b).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown important differences for many traits among the most common breeds of swine. Recent investigations have demonstrated that several traits exhibit heterosis from crossing and have shown the relative advantage of two-breed crosses compared to purebreds (Smith and McLaren, 1967;Bereskin et al, 1971;Kuhlers et al, 1972;Johnson et a/., 1973;Johnson and Omtvedt, 1973b). The most marked advantage of two-breed crosses compared to purebreds is for preweaning pig liveability and dam productivity traits.…”
Section: Introductionmentioning
confidence: 99%
“…Specific objectives were to compare the estimate of one-half individual pig heterosis from this study with earlier estimates of heterosis, and to compare the performance of the three types of crossbred dams and sire breeds for litter traits and postweaning performance. Purebred boars and crossbred females were produced at the OSU swine farm at Stillwater from the purebred Duroc, Hampshire and Yorkshire herds that had been established in 1969 (Johnson et al, 1973). All females farrowing were gilts.…”
mentioning
confidence: 99%
“…Similar Johnson e_t , 1973;Fahmy et al, 1976). General combining ability estimates for the Duroc and Hampshire breeds indicated significant advantages for loin eye area, percent fat corrected muscle and days required to produce 85 pounds of fat corrected muscle.…”
Section: Carcass Traitsmentioning
confidence: 83%